Structural relationships between service quality, communication, motivation, and athlete satisfaction in basketball: Indonesia - Fajar Gumilang H.M; Agung Nugroho; Rumpis Agus Sudarko; Fauzi Fauzi; Fajar Sriwahyuniati (CV Rezki Media, 2026)
Background: Many basketball clubs aim to enhance athlete satisfaction through service quality, communication, and motivation; however, empirical evidence validating these factors as measurable constructs remains limited. Objectives: This study examines whether these variables function as latent constructs influencing athlete satisfaction and validates their measurement structure using confirmatory factor analysis. Methods: This study used a quantitative survey and included 263 basketball athletes from various clubs in Sidoarjo, comprising 110 males and 153 females. The participant characteristics focused on players still in the developmental stage who had been actively participating in club training programs for 3 to 6 months, with educational levels ranging from junior high school to college. Participants were selected using purposive sampling. Data were collected using a valid and reliable Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) via AMOS 22. Results: The results demonstrate that service quality (β=0.337, ????=0.000) and communication (β=0.439, ????=0.000) significantly enhance motivation. Furthermore, motivation significantly affects athlete satisfaction (β = 0.582, ???? = 0.000). Crucially, the analysis confirms that motivation mediates the relationship between service quality (indirect effect=0.139) and communication (indirect effect=0.240) on satisfaction. Conclusions: Theoretically, this study confirms motivation as a vital psychological mediator linking managerial inputs to athlete satisfaction. In practice, the findings demonstrate that while high-quality physical facilities provide a necessary structural foundation, they must be integrated with effective, supportive coaching communication to optimally ignite athletes' intrinsic drive and maximize their overall club experience.